2014
DOI: 10.1007/s10509-014-2125-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chorus normal angle on dynamic evolution of radiation belt energetic electrons

Abstract: Gyroresonance between chorus waves and radiation belt electrons is usually evaluated by using the Gaussian wave normal angle (X = tan θ ) distribution. In this study, we examine the influence of peak wave normal angle (X m = tan θ m ) on chorus-electron interaction in the heart of radiation belts L = 4.5. By varying X m = 0, 2, 4, 6, we calculate the bounce-averaged diffusion coefficients, and then simulate the phase space density (PSD) evolution of radiation belt energetic electrons induced by both dayside an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The basic reason for the result above that diffusion coefficients decrease with increasing X m in the medium to relatively high pitch angles lies as follows. As mentioned in previous works [ Zhang et al , ; Xiao et al , ], diffusion coefficients are controlled by the distribution of resonant roots obtained by the resonant condition , and more resonant roots tend to locate in the small whistler mode wave normal angles and lower pitch angles. For the Gaussian wave normal angle distribution, those resonant roots close to X m contribute more to diffusion coefficients than those deviating away from X m , consequently leading to reductions in diffusion coefficients in the medium to relatively high pitch angles as X m increases.…”
Section: Numerical Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The basic reason for the result above that diffusion coefficients decrease with increasing X m in the medium to relatively high pitch angles lies as follows. As mentioned in previous works [ Zhang et al , ; Xiao et al , ], diffusion coefficients are controlled by the distribution of resonant roots obtained by the resonant condition , and more resonant roots tend to locate in the small whistler mode wave normal angles and lower pitch angles. For the Gaussian wave normal angle distribution, those resonant roots close to X m contribute more to diffusion coefficients than those deviating away from X m , consequently leading to reductions in diffusion coefficients in the medium to relatively high pitch angles as X m increases.…”
Section: Numerical Resultsmentioning
confidence: 85%
“…Ding et al [2013] have performed a detailed calculation on how chorus-electron interaction is determined by the peak normal angles at two indicated kinetic energies. Zhang et al [2014] have further examined effect of chorus peak normal angles on outer radiation belt electron PSDs. Using one-dimensional Fokker-Planck diffusion equation, Meredith et al [2007Meredith et al [ , 2009 have shown that plasmaspheric hiss within small and intermediate wave normal angles can contribute to removing energetic electrons from the slot.…”
Section: 1002/2015ja021786mentioning
confidence: 99%